PENGARUH PROSES PACK NITRIDING TERHADAP ANGKA KEKERASAN PERMUKAAN, KEULETAN DAN STRUKTUR MIKRO PADA BAJA SS 400 - Sujita; Pandri Pandiatmi; Fadly Bukhari (Energy, Materials and Product Design, 2023)
The pack nitriding process is a process of increasing the surface hardness of steel by using nitrogen with the help of organic compounds as a nitrogen source in the process. The processed steel is put into a vessel which is usually made of ceramic, glass or aluminum along with a compound used as a nitrogen source. During heating,The organic compounds used in the analysis process are generally stable at temperatures up to 570 oC and removal times of 2 to 16 hours. The purpose of the pack nitriding process is to increase the surface hardness while remaining ductile inside. In this study, nitrogen was added using a pack nitriding process after which it was quenched using water. The elimination times used were 4 and 6 hours with temperature variations of 560°C, 580°C and 600°C and presenting nitrogen for the 150 gram pack nitriding process. The highest hardness value was obtained at 580 °C with a surface hardness value of 234.84 kg/mm2 with 4 hours of removal time. And the highest impact value was shown by the specimen without treatment of 158.3 Joules. The results of testing the chemical composition of the specimens without treatment and after the pack nitriding process showed that there was an increase in the nitrogen element.